Valtion antropologiaa Tutkimuksia ihmisten hallitsemisesta ja vastarinnasta - Tammisto, Tuomas; Wilenius, Heikki (Suomalaisen Kirjallisuuden Seuran Toimituksia, 2021)
What is a state? This volume approaches the question from an anthropological perspective, which means that the starting point of the analysis is not the concept of the state, but instead, what kinds of structures the state consists of, what kinds of effects these structures have, and how states are experienced by the people who inhabit, make, enact, and resist them. The volume introduces a contemporary anthropological approach to the study of the state for a Finnish-speaking audience. This new approach examines the state as a diverse, socially and culturally constructed phenomenon that varies in time and place. Additional aims of the volume are to introduce and translate concepts from political anthropology to the Finnish language, and to make anthropological analyses of the state known to other disciplines that study the state and to the general Finnish-speaking public. Covering a wide variety of ethnographic contexts examining both the effects of the state and the state-like effects of other institutions, the volume contains case studies from Brazil, Uganda, Papua New Guinea, Madagascar, Finland, Bolivia, Cuba, Egypt, Fiji, Solomon Islands, and Ghana. A theoretical introduction presents the development of anthropological thinking with regard to the state and state-like institutions. An afterword reflects on the contribution of the volume in light of the ethnographic context of Indonesia.